Respuesta :
y = 2x - 1
y = -3x - 6
Since y of the first equation is equal to y of the second equation, then what each y is equal to in the two equations is equal.
2x - 1 = -3x - 6
Add 3x to both sides.
5x - 1 = -6
Add 1 to both sides.
5x = -5
Divide both sides by 5.
x = -1
Now substitute -1 for x in the first original equation.
y = 2x - 1
y = 2(-1) - 1
y = -2 - 1
y = -3
Solution: x = -1 and y = -3
y = -3x - 6
Since y of the first equation is equal to y of the second equation, then what each y is equal to in the two equations is equal.
2x - 1 = -3x - 6
Add 3x to both sides.
5x - 1 = -6
Add 1 to both sides.
5x = -5
Divide both sides by 5.
x = -1
Now substitute -1 for x in the first original equation.
y = 2x - 1
y = 2(-1) - 1
y = -2 - 1
y = -3
Solution: x = -1 and y = -3